Anthropologie de la démonstration - Claude Rosental (Revue d'anthropologie des connaissances)
In this paper, I analyze how contemporary demonstrations are produced and used, especially in the deductive sciences. Contemporary demonstrations may consist for example in written proofs or in public demonstrations of technology. I underline various roles played by demonstrations and the ways in which they operate in different domains of social life - not only in the field of knowledge production. I show that demonstrations can’t be simply analyzed in terms of proof and persuasion. Demonstrations may be used for example as an observatory, as a transactional instrument, as a project management tool, as a capitalizing device, or as a way to build or manage relations. This study thereby shows the existence of a large research field on anthropological properties of demonstrations in various domains of social life. This research field calls for investigations that need to be as thorough as the studies carried out on epistemological properties of demonstrations.